Embigin is involved in the regulation of early mouse kidney development - Talvi, Salli; Jokinen, Johanna; Rappu, Pekka; Leppäkoski, Roni; Kurtzeborn, Kristen; Rantakari, Pia; Kuure, Satu; Heino, Jyrki (Springer Nature, 2026)
Embigin (Gp70) is a transmembrane glycoprotein that serves as an ancillary protein for monocarboxylate transporters and functions as a fibronectin receptor. In mice, embigin is associated with the regulation of stem and progenitor cells as well as embryonic development. Our study demonstrates that embigin has a prominent role in early mouse kidney development. We found that during early kidney morphogenesis, embigin protein is present in the ureteric bud (UB) and differentiating nephron precursors. Notably, the absence of embigin retards UB branching. In the E13.5 Emb−/− kidneys, we observed a downregulation of genes linked to nephron development, including those involved in podocyte development. However, by E17.5, we found no significant transcriptional or morphological differences, suggesting a transient delay in the Emb−/− kidneys. Furthermore, reanalysis of mouse embryonic single-cell RNA sequencing data revealed that embigin is expressed in renal primordial cells as early as E8.75. Additionally, in embigin knockdown mouse epithelial cells, we noted a downregulation of genes central to kidney development and function, including Pappa2, Acta2, and Tagln, which are also downregulated in the E13.5 Emb−/− kidneys. Overall, our findings indicate that embigin plays a significant role in mouse early development by supporting the functions of tissue-specific stem cells.